Optimal mean corpuscular haemoglobin (MCH) cut-off value for differentiating alpha plus and alpha zero thalassaemia in thalassaemia screening - Idris, Faridah; Chiu, Yee Liew; Seman, Zainina; Mahmud, Noraesah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: The aim of thalassaemia screening is to reduce thalassaemia syndromes with significant clinical implication. Therefore, detection of α0 thalassaemia with two genes deletion is clinically more important than α+ thalassaemia with one gene deletion. The aim of this study is to determine the mean corpuscular haemoglobin (MCH) cut-off point for α0 thalassaemia screening. Method: A total of 688 α0 and α+ thalassaemia cases confirmed by DNA analysis were analysed. Red cell indices (MCV, MCH, RBC, Hb) were retrieved from the laboratory information system. Receiver operating characteristic (ROC) curve is generated to determine the MCH cut-off point for α0 thalassaemia. The diagnostic performance of MCH cut-off value was evaluated with a validation group comprising 100 samples of alpha thalassaemia carriers. Results: ROC curve analysis with area under the curve (AUC) of 0.969 showed that MCH at cut-off of 23.5pg has high sensitivity and specificity in detecting α0 thalassaemia with 98% sensitivity and 85% specificity. Conclusion: MCH cut-off value of 23.5pg can be adopted as the cut-off point for α0 thalassaemia screening to detect clinically significant thalassaemia syndrome and reduce cost and burden of screening.